The knowledge paradox: an inverted U-shaped association between HIV knowledge and stigma among older men in Sichuan Province, Southwest China - Ye, Zhihua; Peng, Jin; Liang, Shu; Li, Yuan; Yuan, Jiang; Zhang, Ruixi; He, Jia; Li, Shuangru; Yang, Bihui; Zhang, Xiaochun; Yang, Yi (Frontiers in Public Health, 2025)
BackgroundOlder men (≥50 years) in China face elevated HIV infection risks, yet HIV stigma remains a significant barrier to prevention. Although HIV knowledge is frequently assumed to reduce stigma, the evidence is inconsistent. This cross-sectional study examined the association between HIV knowledge and stigma among older men in Southwest China, specifically investigating potential nonlinear patterns within sociocultural contexts.MethodsWe conducted a cross-sectional survey from July to August 2023 in three high-HIV-burden areas of Sichuan Province. Using a multi-stage cluster random sampling design, 841 HIV-negative men completed structured interviews. All analyses incorporated survey weights to ensure representativeness. HIV knowledge was assessed via a validated 8-item scale (score range 0–8). Stigma was measured with an adapted 10-item scale (score range 10–50). Survey-weighted hierarchical linear regression was used to test linear and quadratic associations adjusted for covariates. Survey-weighted segmented regression analyses confirmed robustness.ResultsThe weighted mean HIV knowledge score was 4.39 (SD = 2.13), and the weighted mean stigma score was 31.78 (SD = 5.60). Regression analysis revealed an inverted U-shaped association. Stigma initially increased with increasing knowledge (linear β = 1.71, p < 0.001), peaked at a knowledge score of 4.14, and subsequently decreased with increasing knowledge gain (quadratic β = −0.21, p < 0.001). Robustness analyses confirmed differential knowledge-stigma associations across knowledge levels (interaction β = −1.47, p < 0.001). Lower stigma was independently associated with non-rural household registration (β = −2.39, p < 0.001), access to a greater number of HIV health education channels (2–3 types: β = −1.07, p < 0.01; ≥4 types: β = −2.29, p < 0.05), and more liberal sexual attitudes (β = −0.19, p < 0.001). Social support and socioeconomic status were not associated.ConclusionAmong older Chinese men, HIV knowledge has an inverted U-shaped association with stigma. Initial knowledge acquisition correlates with heightened stigma, potentially reflecting sociocultural interpretations of fragmented information. Only beyond a specific threshold does further knowledge correlate with reduced stigma. Interventions may need to be staged or tailored based on individuals’ existing knowledge levels, addressing both the nonlinear knowledge-stigma dynamic and underlying sociocultural norms.